PECULIARITIES OF THE APPLICATION OF THE LEGAL INSTRUMENT OF SUBSTITUTION OF THE DEFENDANT IN ADMINISTRATIVE PROCEEDINGS (VERITAS LEGIS JOURNAL, 2026)
This article analyzes the specifics of applying the legal instrument of substitution of defendant in administrative proceedings. It examines the legal nature of this instrument, its purposes, and its importance for ensuring effective judicial protection of the applicant's rights. Particular attention is paid to the criteria for determining the proper defendant, the procedural grounds, and the procedure for replacing the defendant. The article draws on judicial practice and legal statistics on the application of this principle in administrative proceedings. It also highlights the categories of disputes in which plaintiffs most frequently requested the court to replace the defendant. Conclusions have been drawn regarding the need for a uniform approach to the application of this institution in order to strengthen the principles of administrative justice and ensure proper protection of citizens' rights in the sphere of public law disputes.
Keywords: Administrative procedural code; administrative justice; court; replacement of defendant; plaintiff, defendant; legal proceedings